The Concept of Nation, Seen by George Sofronie and the Actuality of the Debate in the Contemporary Context - Alexandru Jadaneant (CES Working Papers, 2011)
The present article introduces the reader to the concept of nation provided by the great Romanian jurist George Sofronie. Sofronie can be seen as the ”father” of the Romanian international public law school, because he is the one, who has written in Romania an handbook in these field. Sofronie debates on the problem of nations and of protected minorities. These are issues that are also very discussed in the field of the european integration process.
Keywords: 330; Nation; European Union; principle of nationalities; minorities Romania